Customer Service In An Auditor-Auditee Relationship - Kitindi, E.G.; Gunda, M. (Accounting Department,, 2004)
Drawing on marketing concepts, this study was undertaken to determine whether auditors in Botswana have positioned themselves to provide the best customer service to their clients. Auditors in Botswana are found to be concerned about customer service and retention, and have instituted measures that are expected to enable them provide quality service. In addition to adherence to professional and statory requirements, auditors provide some other services beyond auditing. The study ï¬nds out however that auditor and their clients have different perceptions on auditors responsibilities. Suggestions are given at the end to bridge this perception gap. Keywords: Auditors, auditees, customers service, customer relationship. Expectation gap.